2022
DOI: 10.53730/ijhs.v6ns5.10544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of correlation between serum βTP and cystatin C as biomarkers for the detection of early nephropathy in Iraqi patients with type 2 diabetes

Abstract: Background: Diabetic nephropathy (DN) is one of the most well-known diabetic microvascular complications, affecting around 40% of individuals with type 2 diabetes mellitus (T2DM). It progresses to end-stage renal disease (ESRD), and its primary detection can be done via diabetes biomarkers. The power of early biomarker identification of DN in T2DM serum is evaluated in this study. Aim: This study aimed to assess the possibility of using ΒTP and Cys. C as earlier markers for the detection of nephropathy in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Patients and healthy control: included 120 subjects from both sexes (female and male), which is the into four groups according‫ا‬ to their (UACR‫. )ا‬ the clinical‫ا‬ characteristics of the four study groups statistically significant difference was shown in the table (2). Participant were divided‫ا‬ into four groups according‫ا‬ to Albumin Creatinine Ratio (ACR) and HbA1c, the mean ± SD difference of S. Cys C and S. BTP between the 4 groups was assessed using ANOVA test.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients and healthy control: included 120 subjects from both sexes (female and male), which is the into four groups according‫ا‬ to their (UACR‫. )ا‬ the clinical‫ا‬ characteristics of the four study groups statistically significant difference was shown in the table (2). Participant were divided‫ا‬ into four groups according‫ا‬ to Albumin Creatinine Ratio (ACR) and HbA1c, the mean ± SD difference of S. Cys C and S. BTP between the 4 groups was assessed using ANOVA test.…”
Section: Resultsmentioning
confidence: 99%
“…BTP in compare to microalbuminuria and normoalbuminuria all in compare to healthy control , as presented in table (2). Using the Pearson correlation coefficient, the relationship between S. BTP and S. Cys C. in the three diabetics groups was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations